1993
DOI: 10.1152/jappl.1993.75.1.173
|View full text |Cite
|
Sign up to set email alerts
|

Sprint training increases human skeletal muscle Na(+)-K(+)-ATPase concentration and improves K+ regulation

Abstract: This study investigated the effects of sprint training on muscle Na(+)-K(+)-adenosinetriphosphatase (ATPase) concentration, plasma [K+] regulation, muscle performance, and fatigue during severe intermittent exercise. Six untrained male subjects underwent intensive cycle-sprint training for 7 wk. Muscle biopsies were taken at rest from the vastus lateralis muscle before and after 7 wk of training and were assayed for Na(+)-K(+)-ATPase concentration using vanadate-facilitated [3H]ouabain binding to intact sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
179
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(199 citation statements)
references
References 0 publications
18
179
2
Order By: Relevance
“…Subjects completed four 30-s maximal exercise bouts (EB1-4) (each separated by 4 min rest) on a cycle ergometer. Supervised high-intensity cycling training (5,15,16) was then conducted thrice-weekly for 7 weeks. The number of cycle bouts per training session progressed from 4 in week 1 to 6 in week 2, 8 in week 3, and 10 in weeks 4 -7.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects completed four 30-s maximal exercise bouts (EB1-4) (each separated by 4 min rest) on a cycle ergometer. Supervised high-intensity cycling training (5,15,16) was then conducted thrice-weekly for 7 weeks. The number of cycle bouts per training session progressed from 4 in week 1 to 6 in week 2, 8 in week 3, and 10 in weeks 4 -7.…”
Section: Methodsmentioning
confidence: 99%
“…67 It is thus possible that training regimes can take advantage of the force production capacity of skeletal muscles through the implementation of high-intensity sprint training exercises to increase Na + K + -ATPase concentration and thus increase the amount of force produced by muscle fibers on stimulation. 68 The polymorphism of subjects expressing homozygous Gly16 alleles demonstrated greater potential for trainability because of higher aerobic performances and increased responses to exercises. 38 Snyder et al 20 also proposed that the Gly16Glu27 haplotype represents a more positive response to exercise.…”
Section: The Influence Of the Environment On Potential Trainability Omentioning
confidence: 99%
“…One randomized controlled trial reported increases of Na, K-pump content [21], which has been demonstrated to be low in patients with type 2 diabetes compared to healthy adults [45,46] and has been reported to increase both with endurance and sprint training in healthy individuals [47][48][49][50][51][52]. The intracellularly produced lactate leaves the cell via simple diffusion and two proteins: monocarboxylate transporter (MCT) 1 and MCT4 [53].…”
Section: Othersmentioning
confidence: 99%